Translation Techniques Analysis of Commissive Speech Act in Political News - Setiani nur rosidah; Irawan Saleh Wijaya; Kalista Diah Tantri; Iriananda Jete Miranda (Jurusan Sastra Indonesia, 2020)
ABSTRACTLately, media are spreading everywhere and the information provided is accessed by all the people around the world. Therefore, that information should be presented accurately. This research paper is aimed at identifying the role of commissive speech act in political news. Journalism language is used to split the information on political news.A lot of politicians use promises in their speeches to gain sympathy and trust from their audience, society. Promise, threat, guarantee, offer, and refusal are examples of the utterances done in commissive speech act.This research paper employed a qualitative method by analyzing the descriptive text of political news. The data are taken from political news in both language of source and target text after that the researcher analyzes to examine commissive speech act found on political news text. In translating the political news, in order to get a good result in the target language, various techniques of translation are needed, such as transposition, generalization, amplification, and literal translation. There are no significant difficulties in translating political news. Still, if the message in the source text is not delivered correctly, the news will be considered a hoax.Keywords: commissive, speech act, political news, translation, equivalence.